The Phenomenon of Vaping in Female Students - Ruth Christina Indriani; Farid Aulia; Sianturi, Putri Adliani; Putri Sundari; Br Sembirng, Sersa Ulina; Milala, Yesi Yandira; Pasaribu, Desi Natalia; Ananda Putri (Indonesian Journal of Medical Anthropology, 2023)
In its development, vaping is not only in demand by men, but women have also become its users. Some societies still stigmatize women who smoke or vape. Women who vape or smoke are often referred to as unrighteous or naughty women and get ridiculed or cursed. In fact, vaping behavior in women is inseparable from the motives that are their reasons for vaping. The purpose of this study is to find out what the motives of women for vaping are, what effects are obtained after using vaping, and what stigma is obtained. The research was conducted using a qualitative approach with primary and secondary data collection techniques. Primary data collection was conducted through an in-depth interview method (a departmental interview) by finding three key informants. The informant requirement is a woman who is a vape perpetrator. secondary data in this study using a review of online literature. The database used is in the form of Google Scholar, where the author combines words relevant to themes such as "Vape and Women," "Motif," and "Stigma." The results of the study concluded that one of the reasons women vape is to think that vaping is something cool. Faster fatigue and shortness of breath are two of the effects they receive after vaping. Women who vape also often receive negative ratings from the surrounding community; they are often said to be bad women.